G(x)=e^x-5

The graph is shifted 5 units downwards.

The horizontal asymptote is at y= -5 as it used to be at zero but as the entire graph is shifted downwards, so it went

from y=0 to y = -5.

the y intercepts is when x = 0

therefore,

G(x)=e^x-5

G(0) = (e^0) - 5

= 1 - 5

= -4

so (x,y) = (0,.4)

H(x)=-e^x

The graph is reflected across the x-axis. The horizontal asymptote is in the same place but the y-intercept = (0,-1)

The graph is shifted 5 units downwards.

The horizontal asymptote is at y= -5 as it used to be at zero but as the entire graph is shifted downwards, so it went

from y=0 to y = -5.

the y intercepts is when x = 0

therefore,

G(x)=e^x-5

G(0) = (e^0) - 5

= 1 - 5

= -4

so (x,y) = (0,.4)

H(x)=-e^x

The graph is reflected across the x-axis. The horizontal asymptote is in the same place but the y-intercept = (0,-1)